Digital technologies for economic sustainable development at Chinese enterprises - A.M.; Zheng yang (Економіка, управління та адміністрування)
In the past, there was a lot of traditional enterprises of a great success for a long time, but today, under the rapid development of the social economy, they have to change to cope better with the possibility of the problem, they must be in information technology and digital technology put more money on, they need to combine information technology and management activities. Agriculture is the basis of the sustainable development of the national economy, the necessary demand of human beings, and the basis of human survival. Therefore, the construction and application of information technology have become an important research topic in the new era. Through the research of this paper, we can understand better how to combine digital information technology with enterprise management. The current research applies such analyses as: logical generalization and сomparison that include clarifying and simplifying the concepts of digital technology and enterprise management; expert evaluation, statistical analysis, data grouping and summary aiming at the research on enterprise market situation, identification, and development of digital technology; factor comprehensive analysis as the method of improving efficiency and productivity by applying digital technology in management; and economic mathematical modeling competitiveness model analysis. The application of computer technology can make information digitization. All the information generated in the operation of enterprises, such as enterprise personnel files, enterprise customer resource information, business financial situation, etc., this huge information, if according to the traditional method, will undoubtedly need to consume more human, material, and financial resources, and low efficiency, increase the cost of work. If computer technology is used to process enterprise information, it will be faster and better to digitize information, facilitate information integration and improve work efficiency, and this information will be very easy to be invoked later, avoiding wasting time to search, and greatly saving human resources. The results analyzed and compared by the author are very useful for the empirical evaluation of the survival and development of Chinese enterprises and even the sustainable economic development of the whole country, and can also provide a reference for the future development and transformation of Chinese traditional enterprises. Based on this, the paper puts forward the methods, and the countermeasures of sustainable economic development in the face of the rapid economic development today. The method proposed by the author can achieve the following results: it can better promote the development of China's economy and can provide substantial help for the transformation of traditional enterprises.